DFT Study on the 1:2 Hydrogen-Bonded Complexes of Dimethyl Sulfoxide with Water - Liu, Guo-Dong; Liu, Tao (Asian Journal of Chemistry, 2011)
We study the hydrogen-bonded complexes formed between dimethyl sulfoxide molecule and water molecules (1:2 ratio) using density functional theory at varied basis set levels from 6-31g to 6-311++g (2d,2p). Four reasonable geometries are considered. The optimized geometric parameters and interaction energies for various isomers at different levels are estimated. The infrared spectrum frequencies, IR intensities and the vibrational frequency shifts of monomers and 1:1 DMSO-H2O complexes at B3LYP/6-311++g(d,p) level are also reported.